Pre- and periprocedural imaging predicts technical but not clinical success of prostatic artery embolization using non-spherical PVA particles: insights from the prospective PROEMBO trial - Schmidt, Vanessa Franziska; Grethen, Jil; Pryadko, Mariya; Gildein, Hannah E.; Fabritius, Matthias P.; Nörenberg, Dominik; Kazmierczak, Philipp M.; Cyran, Clemens Christian Joachim; Ayyagari, Rajasekhara; Deniz, Sinan; Wildgruber, Moritz; Seidensticker, Max; et al. (Academic radiology, 2026)
Rationale and Objectives - To evaluate technical, clinical, and imaging success following prostatic artery embolization (PAE) and imaging-derived predictors of treatment success based on pre- and periprocedural imaging modalities. - Material and Methods - The prospective single-center PROEMBO trial included 119 patients with symptomatic benign prostatic hyperplasia (BPH) undergoing PAE using non-spherical polyvinyl alcohol (PVA) particles. Pre- and periprocedural imaging included CT angiography (CTA), digital subtraction angiography (DSA), and cone-beam CT (CBCT). Technical success, clinical improvement (IPSS, QoL, ICIQ-SF, IIEF-EF), and imaging success (prostate volume reduction) were assessed at baseline and 1-, 6-, and 12 months of follow-ups. Imaging-derived predictors included prostatic artery anatomy, atherosclerotic plaque burden, iliac artery tortuosity, and intraprostatic density measurements after contrast administration. - Results - Median prostate volume was 66 mL (IQR, 49.5-96.5mL). Bilateral embolization was achieved in 96/119 (80.7%), unilateral embolization in 18/119 (15.1%), and bilateral failure occurred in 5/119 patients (4.2%). IPSS improved by median of 7 points (IQR, 2-10) at 1 month, 7 points (IQR, 2.5-13) at 6 months, and 5 points (IQR, 2-12) at 12 months. MRI-based prostate volume significantly decreased by median of 6 mL (IQR, 0-16 mL), 7.5 mL (IQR, −0.75-20mL), and 3 mL (IQR, −2-17mL). Technical failure was significantly associated with number (p=0.003) and cumulative area (p=0.002) of calcified lesions along vascular access route. Iliac artery tortuosity differed significantly between groups, with higher angulation observed in patients with technical failure, e.g., bilateral angle sum of iliac bifurcation: 67.6±21.2 vs. 87.8±24.3 (p<0.001). PA anatomical variants, dominance patterns, and CTA-/CBCT-based density measurements showed no significant correlation with technical outcome (all p>0.05). - Conclusion - Pre- and periprocedural imaging offers valuable predictors of technical success in PAE. Atherosclerotic plaque burden and iliac artery tortuosity serve as practical markers for technical failure, thereby aiding patient selection and procedural planning.